Recurrent pain after laparoscopic surgery for ovarian endometrioma: Clinical features and long-term follow up - Yushi Wu; Yi Dai; Jinghua Shi; Shiqing Lyu; Zhiyue Gu; Chenyu Zhang; Hailan Yan; Jinhua Leng; Xiaoyan Li (European Journal of Obstetrics & Gynecology and Reproductive Biology: X)
Purpose: We aimed to examine the clinical characteristics of patients with ovarian endometriosis (OMA) who were diagnosed with recurrent pain after laparoscopic surgery in an 8- to 12- year postoperative follow-up. Methods: We retrospectively analyzed data of 45 OMA patients with recurrent pain, including a minimum 8 years of post-laparoscopic follow-up reports. All laparoscopic cystectomy procedures were performed by the same surgeon at Peking Union Medical College Hospital between January 2009 and April 2013. Clinical data were retrieved to analyze patients' preoperative characteristics, relevant surgical findings, and postoperative outcomes at follow-up. Results: A total of 45 patients with OMA were included, with a mean age of 31.8 ± 4.92 years. The mean recurrence period was 45.78 ± 24.89 months. Before surgery, 60 % (27/45) of patients had severe dysmenorrhea. During surgery, 93.3 % (42/45) of patients were in stage III/IV, 51.1 % (23/45) had coexisting adenomyosis, and 66.7 % (30/45) had deep infiltrating endometriosis (DIE). For the whole study group, mean follow-up time was 121.96 ± 15.55 months. All patients underwent postoperative medical treatment. The mean recurrence period was 45.78 ± 24.89 months. Cyst recurrence was presented in 24.4 % (11/45) of patients, while 75.6 % (34/45) only complained of pain recurrence. At the end of follow-up, spontaneous pregnancy was seen in 24.4 % (11/45) of patients and 6.7 % (3/45) received in vitro fertilization and embryo transfer (IVF-ET). Conclusions: Patients with symptomatic recurrence after surgery had more severe dysmenorrhea, larger proportion of coexisting adenomyosis and DIE, and a higher revised American Fertility Society (rAFS) stage. Recurrence of endometrial cysts was not related to pain recurrence. Long-term postoperative pharmacological therapy is recommended to reduce recurrence.